Education Advantages Of Using Robots In The System - Ravshonbek Otonazarovich Sultanov (Euro Asian Journal Publishing, 2024)
In the article roboticist devices , Arduino UNO boards using devices connect and them textbook as insert efficiency about feedback given
Keywords: Arduino; UNO; interface; sketch